Unveiling Digital Leadership: Exploring Models and Theories - Ming, Goh Kok; Mansor, Mahaliza (South Asian Journal of Social Sciences and Humanities, 2024)
Digital leadership has emerged as an essential strategy in addressing the demands of the digital era. This study reviews academic research on digital leadership models and theories, drawing from published articles in the field. This study has synthesized existing research to create a robust framework that integrates transformational and distributed leadership principles. The framework clarifies the essential components of effective digital leadership and provides practical guidance for organizations navigating the digital landscape. By combining insights from various leadership theories with current digital practices, this research improves our understanding of leveraging technology for organizational success. Moving ahead, it is crucial to empirically validate and apply this framework to verify its effectiveness and adaptability in diverse contexts. The research findings lay the foundation for further exploration of digital leadership strategies, enabling sustainable digital transformation in organizations. The proposed model presents opportunities for future research to explore the broader impact of digital leadership on digital transformation.